Image quality assessment using NEMA NU 4/2008 standards in small animal PET scanner - Rodrigo Modesto Gadelha Gontijo; Andréa Vidal Ferreira; Juliana Batista Silva; Marcelo Henrique Mamede (Brazilian Journal of Radiation Sciences, 2019)
In Brazil, there are few microPET in use and a quality control protocols standardization are needed to harmonize their use in the research field. Thus, the purpose of this study is to characterize the image quality performance of the microPET scanner (LabPET 4, GE healthcare Technologies, Waukesha, WI) using the NEMA NU 4/ 2008 standards and specific phantom. The NEMA image-quality (IQ) phantom consists of 3 different regions to analyze distinct characteristics: image noise (%SD), expressed as percentage SD in a uniform region (%SD), recovery coefficient (RC) and Spill-over (SOR) in air and water. The IQ phantom was filled with 18F-FDG calibrated at the beginning of acquisition, placed in the center of the field-of-view (FOV) and measured with the typical whole body imaging protocol. The images were reconstructed with different reconstruction methods (FBP-2D; MLEM-3D and OSEM-3D); with and without high resolution (HR) when possible. The results were compared. The LabPET 4 system produces appropriate image and with performance according to the literature. The present study is an initial step to verify the NEMA NU 4/2008 use in the Brazilian scenario for further standardization.